Functional Advantages of Porphyromonas gingivalis Vesicles - Ho, Meng-Hsuan; Chen, Chin-Ho; Goodwin, J. Shawn; Wang, Bing-Yan; Xie, Hua (PloS one, 2015)
Porphyromonas gingivalis is a keystone pathogen of periodontitis. Outer membrane vesicles (OMVs) have been considered as both offense and defense components of this bacterium. Previous studies indicated that like their originating cells, P. gingivalis vesicles, are able to invade oral epithelial cells and gingival fibroblasts, in order to promote aggregation of some specific oral bacteria and to induce host immune responses. In the present study, we investigated the invasive efficiency of P. gingivalis OMVs and compared results with that of the originating cells. Results revealed that 70-90% of human primary oral epithelial cells, gingival fibroblasts, and human umbilical vein endothelial cells carried vesicles from P. gingivalis 33277 after being exposed to the vesicles for 1 h, while 20-50% of the host cells had internalized P. gingivalis cells. We also detected vesicle-associated DNA and RNA and a vesicle-mediated horizontal gene transfer in P. gingivalis strains, which represents a novel mechanism for gene transfer between P. gingivalis strains. Moreover, purified vesicles of P. gingivalis appear to have a negative impact on biofilm formation and the maintenance of Streptococcus gordonii. Our results suggest that vesicles are likely the best offence weapon of P. gingivalis for bacterial survival in the oral cavity and for induction of periodontitis.